Indução halofílica de comunidade microbiana para biodegradação de microplásticos em ambientes marinhos - Ivo, Valéria de Souza (Universidade Federal de São Carlos, 2023)
The development of technologies to combat microplastics in the marine environment contributes to achieving the goals of the Ocean Decade in the 2030 Agenda. In this context, this research explores the degradation efficiency of microplastics (5 mm) of the polypropylene (PP) type by halophiles induced from the soil simulating marine conditions (salinity 3.5%) as an optimized alternative for depollution, evaluating microbial degradation through the evolution of CO2, given that soil microorganisms have nutritional plasticity and can seek alternative sources of food and when capable of survive environments with high salinity are classified as halophilic microorganisms, this class being more likely to degrade polymers. The use of PP as a material to be degraded is due to the fact that it is one of the most produced non-biodegradable plastic materials worldwide and its presence in the oceans is also the largest. Therefore, the four bacteria were selected from soil collected on the premises of UFSCar-CCA (Araras) and induced into the simulated marine environment. These bacteria were part of the respirometric biodegradation tests, lasting 56 days, in which weekly titrations were carried out to measure CO2 production, this being the main method chosen to evaluate the biodegradation of PP. The material was subjected to two treatments: one with exposure to UV (PPt UV) and the other without treatment (PPi). Subsequent tests verified the interaction and transformations in the polymer, such as (i) colorimetry, (ii) Fourier transform infrared spectroscopy (FTIR), (iii) scanning electron microscopy (SEM), (iv) the percentage of mass loss, (v) substrate consumption tests in solid media to evaluate the presence of microorganisms embedded in the PP after biodegradation, and (vi) ecotoxicity tests with Lactuca sativa. The results of biodegradation through the production of CO2 indicated activity for all four isolates, identified as AS1, AS3, AS4 and AS5, with the AS1 and AS4 strains being the most effective in degrading PP. The data regarding the biodegradation of PP by the AS1 lineage, when it consumes PPt (UV) and PPi, obtains a higher production of CO2, with a difference of 28.3% and 20%, respectively, more compared to the control group in that the AS1 lineage is found consuming only the culture medium and when comparing the PPt (UV) and PPi data associated with the AS4 lineage it is possible to observe an increase of 17% more when the PP undergoes UV treatment. Another interesting fact is the toxicity present in the substrate resulting from the biodegradation of PP on all strains, proving that the degradation pathways of this polymer must be explored in order to develop better studies. Therefore, from this experiment, the evaluation of the biodegradation of PP by soil microorganisms induced in the marine environment, brought significant biodegradation results, mainly from the AS1 and AS4 lineages, obtaining an even greater oxidative degradation when the PP is treated with UV, reveal are microorganisms with great biotechnological potential for PP degradation in marine waters. This research also contributes to more in-depth discussions about the adaptation mechanisms of microorganisms and their multiple functionalities, in addition to proposing studies on the toxicity of biodegradation byproducts with other test organisms.
Halophilic induction of microbial community for biodegradation of microplastics in marine environments
Keywords: Oceano; Microrganismos de solo; Indução; Biodegradação; Polipropileno; Ocean; Soil microorganisms; Induction; Biodegradation; Polypropylene; CIENCIAS BIOLOGICAS::MICROBIOLOGIA